The Development of Hedge Funds and Their Operation in Stock Markets in China - LI, ZIXIN (2013)
Currently, the term ‘hedge funds’ in China is still a new word to the public. The development of hedge funds is relative slow. This dissertation discusses the development of hedge funds in China and makes an empirical research on the stock market using feasible strategies. It is concluded that not all strategies are feasible in China with regard to the local financial market and regulations; therefore, limitation may exist. The financial market is not mature, for example, there are some barriers of law and the cultivating of talents is imperfect. Finally, suggestions are also given to give a better environment for the development of hedge funds.